Pengaruh pembelajaran dwi bahasa terhadap peningkatan kemampuan bahasa mahasiswa di uin malang - Ula, Rofi Maf (Maliki Interdisciplinary Journal, 2025)
PKPBA (Special Program for Arabic Language Lectures) and PKPBI (Special Program for English Language Lectures) are compulsory courses for all new students at UIN Maulana Malik Ibrahim Malang. These two programs are managed by the Language Development Center (PPB) and are designed to equip students with adequate Arabic and English language skills, as a provision for facing the academic and professional world. PKPBA focuses on developing Arabic language competence, while PKPBI, also known as the One Year English Program, emphasizes intensive improvement in English.This study aims to analyze the effect of PKPBA and PKPBI program implementation on improving students’ language skills. In addition, it explores the barriers encountered in the implementation of the programs and offers optimization strategies so that the main objectives of the programs are maximally achieved. By looking at the important role of this program in producing “plus-plus scholars” who are competent in foreign languages, the findings in this study are expected to be material for evaluation and development of the language learning system at UIN Malang.